1985
DOI: 10.1111/j.1365-2125.1985.tb02748.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxprenolol and metoprolol Oros systems in the dog: comparison of in vivo and in vitro drug release, and of drug absorption from duodenal and colonic infusion sites.

Abstract: 1 The performance of oxprenolol and metoprolol Oros systems has been evaluated in the dog. One study compared in vivo and in vitro release from both systems over 2-14 h. The other compared the systemic availabilities of both drugs after 3 h infusion at a constant rate into the cephalic and hepatic portal veins, and into the lumen of the duodenum and colon. 2 In the in vivo release studies, Oros systems were recovered throughout the gut from the stomach to the colon. The amounts of drug remaining in the systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…For high extraction drugs, F firstpass reflects the variability in intrinsic clearance (CL int ) in the liver and/or gut wall . As the medium-to-high extraction drug metoprolol is also partly metabolized in the dog intestine ( E G ≈ 50%), the individual differences in CL int may therefore be a substantial source of both intra- and interanimal variability. , Regardless of this, the interanimal variability in P eff for metoprolol was small compared to the low-extraction drugs atenolol and enalaprilat, indicating that other sources of variability, such as factors affecting the permeation process, were more critical (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For high extraction drugs, F firstpass reflects the variability in intrinsic clearance (CL int ) in the liver and/or gut wall . As the medium-to-high extraction drug metoprolol is also partly metabolized in the dog intestine ( E G ≈ 50%), the individual differences in CL int may therefore be a substantial source of both intra- and interanimal variability. , Regardless of this, the interanimal variability in P eff for metoprolol was small compared to the low-extraction drugs atenolol and enalaprilat, indicating that other sources of variability, such as factors affecting the permeation process, were more critical (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The F firstpass values for atenolol (1.0), enalaprilat (1.0), metoprolol (0.25), and ketoprofen (0.93) were the same in both intestinal segments. The F firstpass values were based on reported literature values and individual plasma CL values from the iv administration. Note that these dog F firstpass values deviate from those in Table , which are from human. P eff was then calculated by relating the site-specific intestinal absorption rate to the remaining API in the lumen and to the intestinal luminal radius (eq ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been documented that dogs have an unsacculated colon and therefore handle the transit of fluid and small particles in a fast way (Sutton, 2004). In 465 contrast to the small pellets in the reference formulation it can be assumed that the larger mini-matrices are retained at the ileocecal junction, increasing the residence time in the ileum which offers a better absorption of the metoprolol tartrate, since it has been demonstrated previously that metoprolol is absorbed to the same degree from the duodenum and colon (Fara et al, 1985). It has been demonstrated that for metoprolol tartrate the co-extruded 470 matrix formulations offer a higher bioavailability in dogs (AUC 3 to 7-fold higher and C max 2 to 7-fold higher) than the reference pellet formulation.…”
Section: In Vivo Evaluationmentioning
confidence: 99%
“…This method of drug delivery, therefore, leads to unacceptably low oral bioavailability. Consequently, various approaches based on the use of protective coatings (97), targeted delivery (98), permeation enhancers (99), protease inhibitors (100), and bioadhesive agents (101-103) have been explored in recent years. While all of these methods have been shown to increase the oral bioavailability of drug molecules, none of them offer a complete solution for adequate and safe oral delivery of peptides and proteins.…”
Section: Mems For Drug Deliverymentioning
confidence: 99%